Pengaruh Disiplin Kerja dan Etika Kerja Terhadap Kinerja Pegawai PT. Pos Indonesia Kantor Cabang Padangsidimpuan - Ya’ti Ikhwani Nasution; Haidir Harianja (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The discussion in this research is related to employee performance, work discipline and work ethics. The type of research used is quantitative research, while the information required by researchers is obtained directly from the research object by distributing questionnaires to 31 respondents. The data collection techniques used by researchers are questionnaire methods, documentation and interviews. The analysis technique used is the validity and reliability test of the instrument, then the data analysis used is the basic assumption test, classical assumption test and hypothesis test using the data processing computer program SPSS 22. The results of the research show that there is an influence of work discipline on the performance of PT employees. Pos Indonesia Padangsidimpuan Branch Office can be seen from implementing time discipline, regulatory discipline and responsibility discipline for each employee which can indirectly improve employee performance. There is an influence of work ethics on the performance of PT employees. Pos Indonesia Padangsidimpuan Branch Office can see the attitudes and behavior, appearance and way of speaking of each employee can also influence the performance of PT employees. Pos Indonesia Padangsidimpuan Branch Office. The conclusion is that work discipline and work ethics simultaneously and partially influence the performance of PT employees. Pos Indonesia Padangsidimpuan Branch Office.